Guidelines for the management of acne: recommendations from a French multidisciplinary group. (20th October 2017) - Le Cleach, L.; Lebrun‐Vignes, B.; Bachelot, A.; Beer, F.; Berger, P.; Brugère, S.; Chastaing, M.; Do‐Pham, G.; Ferry, T.; Gand‐Gavanou, J.; Guigues, B.; Join‐Lambert, O.; et al.
Abstract : Linked Comment:Tan. Br J Dermatol 2017; 177: 892–893